DESIGN AND APPLICATION OF NEW TYPE OF CRANK AUTOMATIC ADJUSTMENT MECHANISM OF PUMPING UNIT - WU JunFei; WANG Qian; JIN Xin; XIAO Shu (Jixie qiangdu)
To lower the labor intensity, reduce energy consumption, improve efficiency, increase the service life of the pumping unit and achieve automatic adjustment of pumping unit, based on the CYJ10-4.2-53 HF type pumping unit, this paper completes the structure and parameter design of the crank automatic balance device. The key transmission part screw is selected and checked based on the fourth strength theory. ANSYS Workbench is used to analyze the finite element strength. It is concluded that the theoretical check is basically as the same as the simulation result, the theoretical calculation is feasible, and the overall structure meets the strength requirements.Finally, the pumping unit is tested in the field, the instrument measured its balance meets the requirements, the energy saving effect is satisfactory, and it has a certain promotion and application prospects.